EP-43 Soup and sweet is not enough to eat: Postoperative nutritional intake is inadequate following open colorectal resection. (9th August 2022) - Hardy, Edward; Quinn, Anna; Bergin, Emma; Phillips, Beth; Lund, Jon
Abstract: Aims: Adequate postoperative nutrition reduces complications and may modulate the metabolic stress response to surgery. In particular, protein intake may reduce loss of muscle mass and function thereby enhancing recovery to a normal functional level. This study aimed to assess the adequacy of nutritional intake in patients following an ERAS protocol after open colorectal resection. Methods: Dietary intake on postoperative day (POD) 1 to 4 was recorded. Energy (Kcal) and protein (g) intake was calculated using information from the hospital's food supplier. Values were compared to the European Society of Clinical Nutrition (ESPEN) guidelines for perioperative patients (25Kcal/kg and 1.5g/kg of protein per day, based on ideal body weights). Results: Eleven patients were recruited. Mean daily energy intake was 490.0Kcal (± 470.7), 505Kcal (± 251.8), 541.0Kcal (± 488.1) and 610.5Kcal (± 900.5) on POD 1–4 respectively. Mean daily protein intake was 13.9g (± 14.1), 14.9g (± 10.2), 15.0g (± 15.6) and 18.5g (± 25.6) on POD 1–4 respectively. Excluding patients who developed ileus (n=4), total energy and protein intakes over POD1–4 were 42.6% (± 19.7) and 21.1% (± 11.4) of the ESPEN recommended daily amount respectively. In patients with ileus these values reduced to 12.8% (± 2.6) and 5.7% (± 0.9). Two thirds of meal choices were soup, jelly or ice cream. Conclusions: Early postoperative nutrition after open colorectal resection in inadequate. Further strategies are required to counteract this. Examples may include protein fortification of popular postoperative meal choices and prehabilitation to improve patient's nutritional reserves.